New paradigm of a company’s competitiveness: complex approach - V. I. Pyatanova (Управление)
The issues of competitiveness such as why some companies reach success, while others not, how companies diﬀer and how they are managed within the chosen strategies to reach the state of competitiveness are the key for the organization of any type and industry. Some researches had a tendency to fragment or disintegrate the important parts of this problem, but the purpose of this paper is to integrate the main elements of the competitiveness phenomenon into the complex system and oﬀer a wide practical view over the cornerstones of a company’s competitiveness in a contemporary environment. In this article the author reveals her understanding of the concept of modern company’s competitiveness, then in the main part oﬀers the qualitative model – the system of company’s competitiveness which should lead to ﬁnancial competitiveness. The presented framework is practice-oriented and based on factors and eﬀorts that depend on the company itself, but goes beyond the resource-based view or a particular single strategy school, highlighting the importance of a complex approach.